2018
DOI: 10.1002/adhm.201801047
|View full text |Cite
|
Sign up to set email alerts
|

Local Delivery and Sustained‐Release of Nitric Oxide Donor Loaded in Mesoporous Silica Particles for Efficient Treatment of Primary Open‐Angle Glaucoma

Abstract: Nitric oxide (NO) donors are ideal drug candidates for reducing intraocular pressure in the treatment of glaucoma. However, poor cornea penetration, short duration of efficacy, and narrow therapeutic index of most NO donors obstruct their clinical applications in glaucoma treatment. This study reports a novel NO donor delivery system based on mesoporous silica nanoparticles that can readily overcome the above difficulties and deliver the NO‐donating drug sodium nitroprusside to the target tissues (trabecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 58 publications
0
44
0
Order By: Relevance
“…The reduced cornea penetration, short duration of efficacy, and limited therapeutic index of most NO donors impede their clinical application in glaucoma therapy. Recent studies reported a novel NO donor delivery system . This method is based on mesoporous silica nanoparticles (MSNs), which may overcome the aforementioned problems and deliver the NO‐donating drug sodium nitroprusside (SNP) to the target tissues, that is, the TM and SC .…”
Section: No's Double‐edged Sword: Beneficial Effects On Ocular Physiomentioning
confidence: 99%
See 2 more Smart Citations
“…The reduced cornea penetration, short duration of efficacy, and limited therapeutic index of most NO donors impede their clinical application in glaucoma therapy. Recent studies reported a novel NO donor delivery system . This method is based on mesoporous silica nanoparticles (MSNs), which may overcome the aforementioned problems and deliver the NO‐donating drug sodium nitroprusside (SNP) to the target tissues, that is, the TM and SC .…”
Section: No's Double‐edged Sword: Beneficial Effects On Ocular Physiomentioning
confidence: 99%
“…Recent studies reported a novel NO donor delivery system . This method is based on mesoporous silica nanoparticles (MSNs), which may overcome the aforementioned problems and deliver the NO‐donating drug sodium nitroprusside (SNP) to the target tissues, that is, the TM and SC . In this respect, it has been proposed that the SNP−MSNs delivery system can induce more exogenous NO and maintain higher NO levels in animal eye models.…”
Section: No's Double‐edged Sword: Beneficial Effects On Ocular Physiomentioning
confidence: 99%
See 1 more Smart Citation
“…Glaucoma is a progressive optic neuropathy caused by retinal ganglion cell death. As a chronic ophthalmic disease, it is characterized by the elevation of the intraocular pressure (IOP), decrease of retinal sensitivity and optic nerve head changing that ultimately lead to decreased vision (Yu et al., 2015; Hu et al., 2018). High IOP is the leading risk factor for the development and progression of this disease, which could seriously lead to irreversible blindness.…”
Section: Introductionmentioning
confidence: 99%
“…The elevation of IOP is caused by the imbalance between aqueous humor secretion and drainage (Zhao et al., 2017; Adams et al., 2018). Glaucoma is becoming a major cause of blindness and approximately 80 million individuals by 2020 have been affected worldwide (Hu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%